"Space Obesity": The Effect of Remoteness on County Obesity. (12th May 2014) - Guettabi, Mouhcine; Munasib, Abdul
Abstract We test if remoteness of a county is one of the environmental factors that contribute to obesity. First, we employ geographically weighted regressions (GWRs) that allow us to observe local or regional patterns. We find that county obesity rate is spatially non‐stationary, remoteness affects county obesity rates, and there are spatial heterogeneities in how distance affects county obesity rates. Next, we refine our estimates of the effect of remoteness on county obesity rate using a random effect model that accounts for county‐level unobserved heterogeneity. Even after accounting for these heterogeneities and state fixed effects, we find measurable impact of remoteness on county obesity rate. Splitting the sample into metro and non‐metro counties, we find that remoteness matters more for the obesity rates in the metro counties.